The Effectiveness of Delegation Leadership and Servant Leadership in Law Firms - Wenny Desty Febrian (Dinasti International Journal of Management Science, 2024)
The article on the effectiveness of delegation leadership and servant leadership in law firms is a scientific literature review article in the legal sphere. The purpose of this writing is to build a hypothesis of the influence between variables which can later be used for further research within the scope of law. The research method used is descriptive qualitative. Data was obtained from previous research that is relevant to this research and sourced from academic online media such as Publish or Perish, Google Scholar, digital reference books and Sinta journals. The results of this article are: 1) The effectiveness of delegation leadership plays a role in law firms; and 2) Servant leadership plays a role in the law firm.